Status of soil-transmitted helminth infections in schoolchildren in Laguna Province, the Philippines: Determined by parasitological and molecular diagnostic techniques. - Mary Lorraine S Mationg (PLoS Neglected Tropical Diseases, 2017)
Soil-transmitted helminths (STH) are the most common parasitic infections in impoverished communities, particularly among children. Current STH control is through school-based mass drug administration (MDA), which in the Philippines is done twice annually. As expected, MDA has decreased the intensity and prevalence of STH over time. As a result, the common Kato Katz (KK) thick smear method of detecting STH is less effective because it lacks sensitivity in low intensity infections, making it difficult to measure the impact of deworming programs.A cross-sectional study was carried out over a four-week period from October 27, 2014 until November 20, 2014 in Laguna province, the Philippines. Stool samples were collected from 263 schoolchildren, to determine the prevalence of STH and compare diagnostic accuracy of multiplex quantitative polymerase chain reaction (qPCR) with the KK. A large discrepancy in the prevalence between the two techniques was noted for the detection of at least one type of STH infection (33.8% by KK vs. 78.3% by qPCR), Ascaris lumbricoides (20.5% by KK vs. 60.8% by qPCR) and Trichuris trichiura (23.6% by KK vs. 38.8% by qPCR). Considering the combined results of both methods, the prevalence of at least one type of helminth infection, A. lumbricoides, and T. trichiura were 83.3%, 67.7%, and 53.6%, respectively. Sensitivity of the qPCR for detecting at least one type of STH infection, A. lumbricoides, and T. trichiura were 94.1%, 89.9%, and 72.3% respectively; whereas KK sensitivity was 40.6%, 30.3%, and 44.0%, respectively. The qPCR method also detected infections with Ancylostoma spp. (4.6%), Necator americanus (2.3%), and Strongyloides stercoralis (0.8%) that were missed by KK.qPCR may provide new and important diagnostic information to improve assessment of the effectiveness and impact of integrated control strategies particularly in areas where large-scale STH control has led to low prevalence and/or intensity of infection.